In search of π π [ P : 2 P:2 ]

Calculus Level pending

1 + 1 2 . 1.4 ( 5.1 ! ) 2 + 1 3 . 1.4.6.9 ( 5 2 . 2 ! ) 2 + 1 4 . 1.4.6.9.11.14 ( 5 3 . 3 ! ) 2 + = b 2 b b 2 a π 1+ \frac{1}{2} .\frac{1.4}{(5.1!)^2}+\frac{1}{3} .\frac{1.4.6.9}{(5^2 .2!)^2}+\frac{1}{4}.\frac{1.4.6.9.11.14}{(5^3 .3!)^2}+\cdots = \frac{b^2 \sqrt{\frac{b-\sqrt{b}}{2}}}{aπ}

Above relation holds for coprime positive integers a a and b b . Find 5 a 8 b 5a-8b

Try this also part 1


The problem is original

Relevant wiki

Let's have a look at this


The answer is 0.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Dwaipayan Shikari
Jan 10, 2021

Above series is n = 0 ( 4 5 ) n ( 1 5 ) n ( 2 ) n n ! = 2 F 1 ( 4 5 , 1 5 ; 2 ; 1 ) \sum_{n=0}^∞ \frac{(\frac{4}{5})_n (\frac{1}{5})_n }{(2)_n n!}=_2F_1 (\frac{4}{5} , \frac{1}{5} ; 2;1) ( a ) n = k = 0 n 1 ( a + k ) (a)_n = \prod_{k=0}^{n-1} (a+k) 2 F 1 ( a , b ; c ; 1 ) = Γ ( c ) Γ ( c a b ) Γ ( c a ) Γ ( c b ) _2F_1 (a,b;c;1) = \frac{\Gamma{(c)} \Gamma{(c-a-b)}}{\Gamma{(c-a)}\Gamma{(c-b)}} Here it is 2 F 1 ( 4 5 , 1 5 ; 2 ; 1 ) = 25 4 Γ ( 1 5 ) Γ ( 4 5 ) = 25 4 π sin ( π 5 ) _2F_1 (\frac{4}{5},\frac{1}{5} ;2;1)=\frac{25}{4\Gamma{(\frac{1}{5})}\Gamma{(\frac{4}{5})}}= \frac{25}{4π} \sin(\frac{π}{5}) sin ( π 5 ) = 5 5 8 \sin(\frac{π}{5}) = \sqrt{\frac{5-\sqrt{5}}{8}} . and Γ ( a ) Γ ( 1 a ) = π sin ( π a ) \Gamma{(a)}\Gamma{(1-a)} = \frac{π}{\sin(πa)}

It is 25 5 5 2 8 π \frac{25\sqrt{\frac{5-\sqrt{5}}{2}}}{8π} Answer is 5 a 8 b = 0 \color{#20A900} \boxed{5a-8b=0}

Proof

Take z = 1 z=1 , then it becomes 2 F 1 ( a , b ; c , 1 ) = Γ ( c ) Γ ( b ) Γ ( c b ) 0 1 t b 1 ( 1 t ) c b a 1 d t _2F_1 (a,b;c,1)= \frac{\Gamma{(c)}}{\Gamma{(b)}\Gamma{(c-b)} } \int_0^1 t^{b-1} (1-t)^{c-b-a-1}dt = Γ ( c ) Γ ( b ) Γ ( c b ) B ( b , c b a ) = Γ ( c ) Γ ( c a b ) Γ ( c a ) Γ ( c b ) = \frac{\Gamma{(c)}}{\Gamma{(b)}\Gamma{(c-b)}} \Beta{(b,c-b-a)} = \frac{\Gamma{(c)} \Gamma{(c-a-b)}}{\Gamma{(c-a)}\Gamma{(c-b)}}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...